Synergistic effect of the verapamil and amphotericin B against Cryptococcus neoformans - Pereira, Thaís C. [UNESP]; do Carmo, Paulo H. F. [UNESP]; de Menezes, Raquel T. [UNESP]; de Oliveira, Haroldo C.; de Oliveira, Luciane D. [UNESP]; Junqueira, Juliana C. [UNESP]; Scorzoni, Liliana [UNESP] (Springer Nature, 2023)
Cryptococcus neoformans is an encapsulated yeast that can cause cryptococcosis and cryptococcal meningitis, which conventional treatment involves antifungal drugs such as polyenes, flucytosine, azoles, and their combinations. However, the high cost, toxicity, and increase in fungi resistance to antifungal agents stimulate the search for therapeutic strategies such as drug repurposing and combination therapy. This study evaluated the activity of the antihypertensive verapamil (VEH) alone and combined with amphotericin B (AmB) against C. neoformans. VEH exhibited antifungal activity against C. neoformans with minimum inhibitory concentration and minimum fungicidal concentration of 118 µg per mL. The combination of VEH and AmB exhibited synergism, reducing at least eightfold both drugs’ concentrations. Moreover, the combination decreased the size and glucuronoxylomannnan content of C. neoformans capsule. However, no difference was observed in ergosterol levels of C. neoformans after treatment with VEH and AmB in combination. Altogether, VEH in combination with AmB exhibits potential as a candidate as for the development of anti-cryptococcal drug.
Keywords: Antifungal; Capsule; Cryptococcus neoformans; Synergism; Verapamil